PELAKSANAAN KEBIJAKAN BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) DI KABUPATEN JOMBANG - Soraya Niah, Najah (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
BPJS health targets provide benefits to all those involved in BPJS, meetingmedical needs of participants, the precautionary principle of sustainabletransparency in financial management BPJS. Many of the problems in itsimplementation, namely the health care system, payment systems, and thequality of health care systems. Purpose of this study is to describe, analyzeand Interpret the implementation of Program Policy BPJS using a modelapproach to the implementation of policies of George Edward III and vanMatter van Horn. Analyze and interpret the limiting factor and drivingforce in the implementation of the Program Policy BPJS Develop modelimplementation of effective policies BPJS Program - efficient fit thepurpose of providing health services to the community. This research wasconducted using qualitative method. Implementation of the marked lack ofcoordination/communication, lack of socialization. The existence of awaiting period the user card BPJS can only be activated one week afterregistration is received and may only select one health facility to obtain areferral and can not go to faskes other and service flow tiered very difficultfor the patient (member BPJS), as well as payment of medical expenses arenot borne entirely by BPJS. Communication - socialization of theadministration and the issue of quality of service is still lacking, the endpeople do not understand the process of administration , patient carefacilities are still limited .Keywords : Health service, implementation, BPJS, Jombang